“No one cares more about your community than you”: Approaches to Healing With Secwépemc Children and Youth - Clark, Natalie; More, Jeffrey; Kenoras-Duck, Lynn; Johnston-Virgo, Duanna; Matthew, Sharnelle

(untitled) - Manuel, Norma; Derrick, Jann (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2020)
This paper shares stories from multigenerational Secwépemc and Indigenous healers (including social work and counselling practitioners) with Secwépemc kinship ties. Each Secwépemc and Indigenous healer works with Secwépemc and Indigenous children and youth in Secwépemcúlucw, the land of the Secwépemc Nation. The work is a form of “ancestor accountability” (Gumbs, 2016), as it is one that is embedded in our kinship relationships and our learning on the land together with our children, family, and Elders. Through the methodological framework of Steseptekwle  – Secwépemc storytelling – together with Red Intersectionality, these stories are examples of new tellings, or re-storying, of the Snine (Owl) story that not only illuminate the ongoing resistance to colonial power, but also of the resurgence and reinstatement of Secwépemc ways of addressing wellness and healing.